The Relationship Between Motivation, Goal Orientation, and Perceived Autonomy Support From the Coach in Young Norwegian Elite Hockey Players - Jakobsen, Arne M. (Frontiers in Psychology, 2022)
Abstract This study investigates the relationship between motivation, goal orientation, and perceived autonomy support from the coach among junior elite hockey players. The study is based upon the theory of self-determination and the goal orientation theory. The first aim of the study was to investigate whether high scores on task involvement and perceived autonomy support from the coach may explain players' intrinsic motivatu\ion. Secondly, we sought to discover whether the most autonomous extrinsic motives may be explained by high scores on task involvement and perceived autonomy support from the coach. Lastly, we investigated whether the most controlling extrinsic motives may be explained by greater ego involvement or ego and task involvement and less perceived autonomy support from the coach. A total of 401 players aged 14–18 took part in the survey. The results show that intrinsic motivation can be explained by high scores on both task and ego involvement. The two most autonomous extrinsic motives – integrated and identified regulation – were explained by task and ego involvement and perceived autonomy support from the coach. The two most controlled motives – introjected and external regulation – were both explained by high scores on task and ego involvement